Isolated Middle-Third Clavicle Fracture Causing Horner's Syndrome: A Case Report and Literature Review - Lin, Chia-Yu; Chang, Hao-Wei; Chang, Yu-Hsuan; Lin, I-Hao; Huang, Hung-Yu; Chang, Cheng-Hsien; Chen, Hsien-Te; Chen, Yi-Wen; Lin, Tsung-Li; Hsu, Chin-Jung (Frontiers in Surgery, 2021)
The pathophysiology of Horner’s syndrome arises due to compression or destruction of the oculosympathetic nerve pathway. Traumatic Horner’s syndrome may indicate lethal neurovascular injury, such as brain stem lesion, cervical spine injury, or carotid artery dissection. The middle-third is the most common type of clavicle fracture. However, the association of the isolated middle-third clavicle fracture and Horner’s syndrome is rare. We report the case of a 47-year-old woman who presented to our emergency department with acute trauma. Severe tenderness and limited mobility were observed in her left shoulder. On radiographic examination, a middle-third clavicle fracture was diagnosed. Ptosis and myosis were also noticed on further examination, and she was subsequently diagnosed with Horner’s syndrome. A survey of the brain, cervical spine, carotid artery, and lung revealed no pathological findings. Surgery for the clavicle fracture was performed two days after the accident. The patient recovered from Horner’s syndrome gradually over the two months following the surgery, and the syndrome completely resolved by the third month. To the best of our knowledge, this is the first report of traumatic Horner’s syndrome caused by an isolated middle-third clavicle fracture. The improved outcome may be attributed to the surgical intervention for middle-third clavicle fracture, which may help release ganglion or neuronal compression.